1994
DOI: 10.1161/01.cir.90.2.928
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific determinants of increased left ventricular mass in the Tecumseh Blood Pressure Study.

Abstract: Background Left ventricular hypertrophy (LVH) defined by either ECG or echocardiographic criteria is a risk factor for cardiovascular morbidity and mortality. A number of determinants of LVH have been described in previous studies, principally male sex, hypertension, obesity, and aortic valvular stenosis. We examined the distribution of LV mass (LVM) in a population of 18-to 42-year-old normotensive men and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(73 citation statements)
references
References 59 publications
6
67
0
Order By: Relevance
“…The means for these parameters found in this study also differed from those in the literature 2,3,5,8,9,12. The differences have greater magnitude if the 95% confidence interval is used to define normality. The other echocardiographic measurements are within the normal values presented in the international literature [2][3][4][5]8,9,12 . At least one Brazilian study using a sample of 32 employees of a hospital, presented numbers similar to those in our study.…”
supporting
confidence: 72%
“…The means for these parameters found in this study also differed from those in the literature 2,3,5,8,9,12. The differences have greater magnitude if the 95% confidence interval is used to define normality. The other echocardiographic measurements are within the normal values presented in the international literature [2][3][4][5]8,9,12 . At least one Brazilian study using a sample of 32 employees of a hospital, presented numbers similar to those in our study.…”
supporting
confidence: 72%
“…A potential limitation of the present study is that the insulin levels were assessed in the fasting state but not in response to glucose loading. Several studies have found a positive association between postload insulin levels or area under the postload insulin curve and LV structural variables (22)(23)(24). In a recent investigation, the HOMA value was related to LV mass in women alone, but this relation was largely accounted for by obesity (9).…”
Section: Discussionmentioning
confidence: 93%
“…The incidence and severity of cardiovascular disease, including LVH, in premenopausal women is lower than in men of comparable age, even after correction for various risk factors. 4 However, the molecular effects of estrogen on ventricular cardiomyocytes, which may account for this clinical observation, are less well understood. Cardiomyocytes express functional estrogen receptors (ERs), and estrogen treatment modulates the expression of cardiac-specific genes.…”
mentioning
confidence: 99%